Impact of the COVID-19 lockdown on intimate partner violence: Issues of non-reporting in Bangladesh. (March 2022) - Mahmood, Nabila; Kamruzzaman, Mohammed; Rahman, Aminur; Reidpath, Daniel D; Akhter, Sadika
Introduction: COVID-19 pandemic induced lockdown as prevention and control measure, forced people globally to limit their movements and to stay at home for extended period of time. The objective of this study was to analyze the impact of lockdown on intimate partner violence in Bangladesh. Methods: We conducted a secondary research by employing a Poisson regression model to estimate the effect of pandemic-led lockdown policy on the change in the number of intimate partner violence-related calls during pandemic using national emergency helpline 999 call logs. Data from January 2019 to May 2020 for 64 districts produced 1088 district-month-year observations which had been used for the main analysis. Results: We found a 46% decrease in the incidence rate of intimate partner violence-related calls during the pandemic after adjusting for year, month, district fixed-effects—suggesting, non-reporting of the violence might have exacerbated during lockdown. Conclusion: While increasing rate of intimate partner violence is one side of issue, non-reporting of it has received less attention and during the lockdown non-reporting might grow large and have severe health impacts for women.